Rehearsal for Reconstruction : the Port Royal experiment - Rose, Willie Lee Nichols. 1927- (Indianapolis : Bobbs-Merrill, 1964)
An account of the first experiment in Reconstruction, the effort of northern missionary abolitionists to assist the abandoned slaves of Sea Island, South Carolina establish schools, train troops, claim land ownership, and accept their status as freed men.
"Notes on sources": p. 409-433.
Keywords: Port Royal (S.C.) Expedition, 1861.; Reconstruction (U.S. history, 1865-1877) -- South Carolina -- Port Royal Region; African Americans -- South Carolina -- Port Royal Region -- History -- 19th century; Slaves -- Emancipation -- South Carolina -- Port Royal Region; Reconstruction (U.S. history, 1865-1877) -- Sea Islands; Sea Islands -- History -- 19th century; Port Royal Region (S.C.) -- History -- 19th century